Internationalization strategy of Quinta dos Termos to China - Costa, Pedro Pinto da (2018)
The underlying project was carried out with the purpose of conducting an internationalization strategy of Quinta dos Termos to China. Thus, this project focuses on exploiting the competitive advantages resources of the firm, followed by China ranking analysis and then selecting the most suitable city, in this case Hong Kong. Furthermore, an implementation strategy is suggested with the most optimal mode of entry and several of activities for a successful internationalization to Hong Kong wine market.